Virtual Reality Analgesia for Pediatric Dental Patients - Atzori, Barbara; Lauro Grotto, Rosapia; Giugni, Andrea; Calabrò, Massimo; Alhalabi, Wadee; Hoffman, Hunter G. (Frontiers in Psychology, 2018)
ABSTRACT Background. Dental procedures often elicit pain and fear in pediatric dental patients. Aim. To evaluate the feasibility and effectiveness of immersive virtual reality as an attention distraction analgesia technique for pain management in children and adolescents undergoing painful dental procedures. Design. Using a within-subjects design, five patients (mean age 13.20 years old, SD 2.39) participated. Patients received tethered immersive interactive virtual reality distraction in an Oculus Rift VR helmet (experimental condition) during one dental procedure (a single dental filling or tooth extraction). On a different visit to the same dentist (e.g., one week later), each patient also received a comparable dental procedure during the control condition “treatment as usual” (treatment order randomized). After each procedure, children self-rated their “Worst pain”, “pain unpleasantness”, “time spent thinking about pain”, “presence in VR”, “fun” and “nausea” levels during the dental procedures, using graphic rating scales. Results. Patients reported significantly lower “worst pain” and “pain unpleasantness”, and had significantly more fun during VR, compared to a comparable dental procedure with No VR. Using Oculus Rift VR goggles, patients reported a “strong sense of going inside the computer-generated world”, without side effects. The dentist preferred having the patients in VR. Conclusions. Results of this pilot study provide preliminary evidence of the feasibility of using immersive, interactive VR to distract pediatric dental patients and increase fun of children during dental procedures.